Integrated operations another tool for achieving operational excellence in the oil and gas sector - Tasmin, R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Activities of the oil and gas sector operations are highly complex, from oil rigs to refining and transportation. It is against this backdrop that companies opt for operational excellence to control the complexities, of which failure to manage the situation, assets, peoples and profit could be lost. This paper is aimed at determining how integrated operations influences operational excellence in the oil and gas sector. This is with a view to help in facilitating effective operational excellence implementation in the oil industry. Quantitavive survey research approach was adopted, questionnaire was used to collect data from 120 respondents. The result shows that all the postulated integrated operations factors have significant effect on operational excellence. It concludes that integrated operations are the way forward for condition monitoring and maintenance of oil sector assets, people and process for optimising production, operational efficiency, reduced health and safety risks and environmental performance. Â© BEIESP.